(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2023)
Introduction. An important characteristic of the production and financial activities of enterprises is the financial condition, the formation of which is influenced by both production and financial and economic activities. The financial condition of the enterprise directly affects its ability to compete in the market environment, its ability to cooperate with business partners. Therefore, the financial condition of the enterprise is an important characteristic of both internal and external environment. The purpose of the article is to substantiate the theoretical aspects of financial analysis for diagnosing and formulating recommendations for strengthening the financial condition of the enterprise in modern conditions. Results. The concept of financial condition is complex and complex, characterizing various spheres of enterprise activity. In the scientific environment there are different approaches to its definition, its main criteria are financial stability, solvency, profitability, optimal distribution of profits, etc. Assessment of the financial condition of the enterprise, as an important component in the process of enterprise management, should be carried out on an ongoing basis using traditional methods of analysis: vertical, horizontal and coefficient, which have advantages and disadvantages. The main method is the coefficient method, which includes a set of indicators in five areas of analysis - property status, financial stability, liquidity, business activity, financial results and profitability. All these indicators have peculiarities of interpretation and compliance with the standards under martial law. Conclusions. The hostilities during 2022 put many enterprises on the brink of existence, the need to find answers to new challenges and quickly solve them, primarily related to the preservation of personnel and ensuring their safety, the preservation of property and facilities, the establishment of new logistics routes and transportation of products, the search for new customers or orders, etc.